Hearing : anatomy, physiology, and disorders of the auditory system - Møller, Aage R. (Academic Press, 2006)
Hearing: Anatomy, Physiology and Disorders of the Auditory System provides detailed information about the anatomy and physiology of the entire auditory system and it describes important aspects of disorders of the middle ear, the cochlea, and the nervous system in a comprehensive manner. Most other textbooks on Hearing are focused on either the periphery or the central nervous system and rarely integrate anatomy and physiology with clinical issues. In the past years, it has become apparent that pathologies of the peripheral parts of the auditory system affect the function of the nervous system.